Colour change with longitudinal compression supports hypothesis of multilayer interference as cause for meat iridescence. (11th June 2020) - Ruedt, Chiara; Gibis, Monika; Barbut, Shai; Weiss, Jochen
Summary: The mechanism of iridescence in meat and meat products is still not fully understood but a widely accepted hypothesis is that it originates from a multilayer interference from sarcomere discs. In multilayer interference, the reflected wavelength is affected by the refraction angles, the thicknesses and refractive indices of the intermittent layers. A variation of these factors should therefore cause a disappearance or shift of iridescent colours. To test this hypothesis, we progressively compressed iridescent rolled fillets of ham longitudinal to the long axes of the muscle fibres and measured the interference colours by reflection spectrophotometry. We observed an interference colour shift from longer to shorter wavelengths and reflection intensity decreased with increasing compression pressure. Our data indicate that the compression decreased the layer thickness, so that constructive interference occurred at shorter wavelengths. The results thus provide support for multilayer interference being a primary cause and mechanism for meat iridescence. Abstract : Schematic diagram of multilayer interference in striated muscle fibres. The alternating thin layers are the A‐bands (dark) with a high refractive index (nA ) and I‐bands (light) with a low refractive index (nI ). Reflected interference color shifts to shorter wavelengths with the reduction of the layer thicknesses (dI, dA ) by longitudinal compression of the fibers.